The relationship between sleep fragmentation, daytime sleepiness and quality of life in OSA and predictors of improvement in quality of life on NCPAP - Bennett, L; Langford, B; Stradling, JR; Davies, R (1997)
Obstructive sleep apnoea (OSA) causes disabling daytime sleepiness and impairs quality of life. Quality of life measures and their improvement on nCPAP treatment may be related to daytime sleepiness and sleep fragmentation. This study investigates tiw relationship between quality of life (using the SF-36), daytime sleepiness and sleep fragmentation and improvement in quality of life on nCPAP treatment. The SF-36 provides several dimensions (eg energy/vitality), totalled as the Physical and Mental Component Summaries (PCS and MCS). 51 patients (46M, 5F) with the full spectrum of upper airway narrowing during sleep from normal to severe OSA (AHI med 24.9 range 0-151 ) had polysomnography with ASDA arousal scoring and autonomic arousal detection (arterial pulse transit time, PTT). The autonomic arousal index was the number of PTT falls per hour of sleep. All subjects completed SF-36 questionnaires and baseline measures of objective daytime sleepiness (Oxford Sleep Resistance (OSLER) test (JSR 6;142-145) and these measures were repeated following 4 weeks on nCPAP. All subjects, including the normals, received nCPAP. Pearson's correlation was used to examine the relationships with quality of life and the response to nCPAP. SF-36(*=p<0.05) OSLER test AHI ASDA PTT PCS 0.3* -0.27 -0.44* -0.38* MCS 0.32* -0.30* -0.36* 0.30* PCS change on nCPAP -0.30* 0.35« 0.54* 0.48* MCS change on nCPAP -0.27 0.31* 0.49* 0.48* Impairment of quality of life in OSA is associated with pre-treatment objective daytime sleepiness and with severity of sleep fragmentation (using both cortical and autonomic indices) and to a lesser extent with respiratory disturbance (AHI). These indices of sleep fragmentation also best predict improvement in quality of life on nCPAP.